The comparative study of conscription in the armed forces - Mjøset, Lars; Van Holde, Stephen (Comparative social research ;, 2002)
This volume contributes to the comparative study of military conscription. Issues discussed include: a conceptual clarification of conscription as distinguished from volunteerism and militia service; the emergence of the citizen soldier model; patterns of anti-militarism before World War I; conscription in third world armies; gender-issues in relation to military service; the present phenomenon of child soldiers in Africa; the decline of conscript armies in Western Europe. A review section discusses the contribution of rational choice theory to the analysis of conscription into military forces.